Mental Disorder and Partnership: the Influence and Potential Burden of Affective Disorders on the Quality of Partnerships - Wieser, Erika; Richter-Schmiedinger, Tanja; Glueckler, Christine; Schmidt, Anika; Volkert, Julia; Reif, Andreas; Kornhuber, Johannes; Biermann, Teresa (Psychiatrische Praxis, 2016)
The aim of the present study was to explore the connection between affective disorders and various aspects of the quality of relationships and their impact on partnerships.In a multi-centric study, we used questionnaires to compare three groups of couples: 23 patients suffering from major depression and their partners, 32 patients with a bipolar disorder and their partners, and 49 healthy couples serving as controls.Regardless of the type of affective disorders, stability of the relationship, felt happiness and other measures of quality of partnership were significantly impaired in couples with an affected partner. Partners of patients experience a higher emotional strain in every day life compared to healthy controls. There was a trend showing that bipolar disorder leads to a greater burden and a higher conflict potential than depression.The present study deals with stabile partnerships in daily life, including severely disabled patients needing in-patient treatment. Taking into account the health status of their partners, we discuss various aspects of happiness, conflict potentials as well as impact on the quality of relationships.
EVALuna:34138